A novel form of progressive retinal atrophy in Swedish vallhund dogs. - Ann E Cooper; Saija Ahonen; Jessica S Rowlan; Alison Duncan; Eija H Seppälä; Päivi Vanhapelto; Hannes Lohi; András M Komáromy (PLoS ONE, 2014)
Inherited retinal degenerations, such as retinitis pigmentosa (RP) and age-related macular degeneration (AMD), represent leading causes of incurable blindness in humans. This is also true in dogs, where the term progressive retinal atrophy (PRA) is used to describe inherited photoreceptor degeneration resulting in progressive vision loss. Because of the similarities in ocular anatomy, including the presence of a cone photoreceptor-rich central retinal region, and the close genotype-phenotype correlation, canine models contribute significantly to the understanding of retinal disease mechanisms and the development of new therapies. The screening of the pure-bred dog population for new forms of PRA represents an important strategy to establish new large animal models. By examining 324 dogs of the Swedish vallhund breed in seven countries and across three continents, we were able to describe a new and unique form of PRA characterized by the multifocal appearance of red and brown discoloration of the tapetal fundus followed over time by thinning of the retina. We propose three stages of the disease based on the appearance of the ocular fundus and associated visual deficits. Electroretinography revealed a gradual loss of both rod and cone photoreceptor-mediated function in Stages 2 and 3 of the disease. In the few dogs that suffered from pronounced vision loss, night-blindness occurred first in late Stage 2, followed by decreased day-vision in Stage 3. Histologic examinations confirmed the loss of photoreceptor cells at Stage 3, which was associated with the accumulation of autofluorescent material in the adjacent retinal pigment epithelium. Pedigree analysis was suggestive of an autosomal-recessive mode of inheritance. Mutations in six known canine retinal degeneration genes as well as hypovitaminosis E were excluded as causes of the disease. The observed variability in the age of disease onset and rate of progression suggest the presence of genetic and/or environmental disease modifiers.